Characterization of magnetron sputtered Si3N4 thin films deposited on Aluminum alloy substrates. (2016) - Kishore Kumar, P.R.; Manikandan, V.N.; Deepak Raj, P.; Sridharan, M.
Abstract: Aluminium alloys, due to its versatile nature used in making auto mobile components. In this study the mechanical properties such as decreased coefficient of friction and roughness are attained using silicon nitride (Si3 N4 ) thin film deposition. The depositions were carried out using the reactive radio frequency (RF) magnetron sputtering in surface treated and untreated samples with RF sputtering power of 70 W. The deposited films show polycrystalline nature with a preferential orientation plane (1112). The crystallite size and the lattice strain were calculated for the films deposited over the surface treated and untreated substrates. Surface morphology of the films deposited on surface treated and untreated substrates were studied using field-emission scanning electron microscopy (FE-SEM) analysis. From sessile drop technique decrease in the angle from 96 to 72° was observed for the film deposited over the surface treated substrate which provides low coefficient of friction.